Direct transdifferentiation of tumorigenic melanoma cells induces tumor cell reversion - Wang, Yiman; Liu, Ke; Zhang, Yuxin; Novak, Daniel; Federico, Aniello; Xu, Cai; Horschitz, Sandra; Vierthaler, Marlene; Sun, Qian; Wang, Nina; Poelchen, Juliane; Steinfass, Tamara; et al. (Cell death & disease, 2025)
Melanoma is an aggressive skin cancer and highly lethal at advanced stages due to its high tumorigenicity and metastatic capacity. Changing the phenotype of cancer cells from one lineage to another, a process called transdifferentiation, leads to tumor cell reversion, which goes along with a drastic reduction of their tumorigenicity. Via ectopic overexpression of four neuronal transcription factors, we transdifferentiated melanoma cells into neuron-like cells expressing neuronal markers and showing a neuron-like morphology. Moreover, the tumorigenic and metastatic potential of transdifferentiated cells in vitro and in vivo was significantly reduced. Transdifferentiated cells were also more sensitive to radiotherapy compared with their parental counterparts. We conclude that transdifferentiation of cancer cells into terminally differentiated neuron-like cells might represent a prospective new therapeutic approach for the treatment of melanoma.
Gesehen am 22.09.2025